(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Through direct intake or contact with contaminated sites, the food chain, drinking contaminatedground water, a reduction in food quality due to phyto-toxicity, and a lack of land suitable for agriculture,heavy metal contamination poses serious risks to humans and ecosystems. This leads to food insecurity.Therefore, every living cell must generally be resistant to heavy metals. We can now exploit the potentialof biological diversity to clean up pollution, a process known as bioremediation, thanks toadvancements in science and technology. The following study’s main goal is to evaluate how endogenicearthworm Pontoscolexcorethrurus and its gut microbiota interact with heavy metal absorption fromcontaminated soil samples.The following study uses a variety of materials and techniques, including thecollection of plant material, the isolation of bacteria from earthworm guts, the analysis of theconcentration of heavy metals in soil samples using atomic absorption spectroscopy, as well as theircharacterization and amplifying metal resistant genes.The findings of the Gram staining test were usedto categorize bacteria as Gram negative bacilli, Gram positive cocci, or Gram positive bacilli. Delftia andS. aureus bacteria were then cultured under cadmium stress to see if their growth patterns underwentany notable changes.The observed changes in the bacterial communities of the earthworms maytherefore be used as a warning sign of potential soil pollution, it is hereby concluded. Bacillus cereusand Delftia sp. can be used to remediate soil that has been contaminated with various heavy metalsbecause they can withstand higher concentrations of heavy metal.